(untitled) (Lex localis - Journal of Local Self-Government, 2025)
India. which has passed several gender-protective laws to protect women from harassment, discrimination along with abuse including Section 498A of the Indian Penal Code, Dowry Prohibition Act of 1961 along with Protection of Women from Domestic abuse Act of 2005. These regulations have been passed with the lofty objective of protecting women against patriarchal control as well as ensuring their dignity along with safety. New evidence along with judicial remarks indicate women are abusing these legal protections to settle personal disputes, obtain undue influence over matrimonial disputes, or taunt partners along with in-laws with unfounded claims. The article criticizes the misuse of gender-based laws in India along with its consequences for justice, interfamily dynamics as well as authenticity of true victims. It goes deep, using case studies along with statistical information, into how provisions that were intended to protect have been transformed in some instances into tools of manipulation. Lalong withmark orders such as Arnesh Kumar v. State of Bihar (2014) along with other reports of the Law Commission have highlighted the escalating abuses of provisions such as Section 498A IPC, requiring tighter regulation as well as accountability provisions. The article acknowledges that women’s rights need to be protected but feels that justice cannot be gender-blind. The misuse of protective legislations without any check does harm the innocent people but also mars the public confidence along with will in such legislations. The research promotes fair reforms, such as compulsory inquiry before arrest, sanctioning for justified false accusations along with gender-neutral models, to make sure the law performs its basic role: protecting the innocent along with punishing the culprit, regardless of gender.